Determinants of Chronic Energy Deficiency: Nutrient Adequacy and Household Food Availability - Hana Nurul Sabila; Asti Dewi Rahayu Fitrianingsih; Fajria Saliha Puspita Prameswari; Delita Septia Rosdiana (PROMOTOR, 2026)
Chronic Energy Deficiency (CED) negatively impacts maternal and fetal health, causing risks such as low birth weight and impaired fetal growth. Key contributors include inadequate nutrient intake and limited household food availability. To assess the relationship between nutrient adequacy and household food availability with CED risk in pregnant women at Pataruman Health Center. A cross-sectional study involved 60 pregnant women from Citapen Village selected by simple random sampling. Independent variables were nutrient adequacy (energy, protein, carbohydrate intake) and household food availability, with CED incidence as the dependent variable. Data were collected via questionnaires and anthropometric measurements and analyzed using multiple logistic regression. Normal pre-pregnancy BMI significantly reduced CED risk (OR = 0.14; 95% CI: 0.03–0.77; p = 0.020). Adequate energy intake lowered CED risk by 93% (OR = 0.07; 95% CI: 0.01–0.53; p = 0.005), and sufficient protein intake also provided protection (OR = 0.26; 95% CI: 0.08–0.84; p = 0.005). Food-secure households showed lower CED risk (OR = 0.08; 95% CI: 0.02–0.40; p = 0.001). Carbohydrate adequacy was not significantly associated with CED (OR = 2.6; 95% CI: 0.4–11.7; p = 0.230) but acted as a confounder. No significant interaction effects were found among variables. Adequate pre-pregnancy BMI, energy and protein intake, and household food security protect against CED. Carbohydrate intake should be accounted for as a confounding factor. These findings support integrated nutrition and food security interventions to enhance maternal health.